Exploring the health literacy of First Nations young adult women - Rempel, Ebony; Donelle, Lorie; Kothari, Anita (Journal of Communication in Healthcare, 2016)
Abstract: Relative to non-First Nations, Inuit, and Métis (FNIM) Canadians, FNIM people have poorer health status. Accessing and comprehending information and services that influence health is a fundamental skill that enables individuals to function within a health care system that expects individuals to play an active role in promoting their health. A qualitative investigation of the health literacy skills and the health information needs of young FNIM adults was conducted. Eight single First Nation mothers living on-reserve were interviewed between February 2012 and September 2012. Data analysis generated main themes and subthemes of: (1) Health Information Needs of First Nations Young mothers; (2) Interpersonal Health Information Resources: (i) Asking the Doctor/Telehealth, (ii) Female Family and Friends; and (3) Online Accessibility and User Skills: (i) Health Information Online, (ii) Social Media, and (iii) Navigation and Computer Skills. Although participants used online and social media resources to access health information, they expressed a lack of confidence in their ability to comprehend accessed information. Strategies to support First Nations young mothers are recommended.